Impact of SNEDDS formulation variables on physical characterization, drug release, and anti-inflammatory activity: a review - Rodhia Ulfa; Benni Iskandar; Gressy Novita; Deni Anggraini; Wira Noviana Suhery; Prima Aulia Putra (Faculty of Pharmacy, Universitas Pancasila, 2026)
Self-nano-emulsifying drug delivery systems (SNEDDS) address the challenges of poor solubility and bioavailability in oral drug delivery. These challenges lead to poor therapeutic results and an increased frequency of dosing. This review assesses the challenges of oral drug delivery due to poor solubility and absorption and the potential of Self-Nanoemulsifying Drug Delivery Systems (SNEDDS) to deliver poorly water-soluble drugs. This also entails an assessment of the formulation components of SNEDDS, particularly oils, surfactants, and co-surfactants, and their influence on the physicochemical properties, release profile, stability, and anti-inflammatory activity of the formulation. A thorough assessment of 25 of the most recent primary studies revealed the significant influence of formulation design on the size and distribution of droplets and their subsequent emulsification, drug release, and bioavailability. Oils that are easier to solubilize, along with high HLB surfactants and co-surfactants, such as PEG 400 and Transcutol, are instrumental in producing smaller, stable emulsions that facilitate permeability. Nevertheless, human pharmacokinetic data are lacking, and challenges remain in the large-scale production of solid dosage forms from liquid SNEDDS. This problem is further complicated by the variability of the excipients. The review highlights the need for standardized predictive models and more refined plans for in vivo validation and excipient development. What is unique is the integration of specific information from formulation optimization with translational pharmacological outcomes. This integration has the potential to greatly improve the design and utilization of SNEDDS, thereby expanding its therapeutic benefits.